Psychological Evaluation of Patients With Cancer Presenting to the Emergency Department With Pain: Independent Predictors of Worse Pain Severity, Interference, and Higher Hourly Opioid Administration. Issue 10 (22nd October 2022) - Azizoddin, Desiree R.; Beck, Meghan; Flowers, K. Mikayla; Wilson, Jenna M.; Chai, Peter; Johnsky, Lily; Cremone, Gabrielle; Edwards, Robert; Hasdianda, Adriana; Boyer, Edward; Schreiber, Kristin L.
Abstract : PURPOSE: Pain is a common complaint in patients with cancer presenting to the emergency department (ED). This prospective study evaluated whether biopsychosocial factors could help predict cancer patients with risk of higher pain severity, pain interference, and opioid consumption. METHODS: Patients with cancer presenting to the ED with a complaint of moderate-severe pain (≥ 4/10-numeric rating scale) completed validated self-report measures assessing sociodemographics, cancer-related treatments, pain severity and interference, medication use, and psychological symptoms (depression, anxiety, pain catastrophizing, and sleep disturbance). Opioids administered and subsequent hospitalization were abstracted. Univariable and multivariable regression analyses assessed factors associated with pain-related outcomes. RESULTS: Participants (n = 175) presented with a variety of cancer types, with 76% having metastatic disease and 42% reporting current outpatient opioid use. Higher pain catastrophizing, lower depressive symptoms, lower income, outpatient opioid use, and historical chronic pain were independently associated with worse pain ( P ≤ .05). Higher pain catastrophizing, anxiety, sleep disturbance, outpatient opioid use, and education were independently associated with worse pain interference ( P ≤ .05). The sole independent predictor of ED opioid administration was outpatient opioid use. Patients taking outpatient opioids were younger, had lower health literacy, worse pain catastrophizing, sleep disturbance, depression/anxiety, and greater rates of metastatic cancer and cancer-related surgery ( P ≤ .05). CONCLUSION: Biopsychosocial factors, particularly pain catastrophizing, remained significantly associated with worse pain outcomes for patients with cancer in the ED even after controlling for demographic and clinical variables. Patient outpatient opioid use was independently associated with worse pain, interference, and greater opioid administration, identifying this as a marker for who may benefit most from adjuvant pharmacologic and behavioral interventions.